CLIPS (Communication Learning in Practice for Scientists): A New Online Resource Leverages Assessment to Help Students and Academics Improve Science Communication - Susan Rowland (American Society for Microbiology, 2018)
The ability to communicate is a crucial graduate outcome for science students; however, crowded curricula and large class sizes make it difficult to find time to explicitly teach foundational communication skills. In response to these challenges, we developed an online resource called Communication Learning in Practice for Scientists, or CLIPS. CLIPS provides a multi-point mentoring model that has allowed us to successfully integrate the teaching and learning of a complex set of tacitly-understood skills across multiple scientific disciplines. It also provides a flexible way for industry experts, academics, and students to learn from one another’s experiences of, and expertise in, science communication. CLIPS leverages the student focus on assessment; students access CLIPS for pragmatic, detailed, and consistent advice when undertaking assessment tasks. In creating CLIPS, our philosophy was that communication is the core business of any scientific practice, not an add-on after the event. Extensive, repeated use of CLIPS by both students and academics indicates that the resource and its delivery model are considered useful, respected, and impactful for, and by, the intended audiences. We have provided CLIPS to the science education community through www.clips.edu.au.